The mental abilities of the Guilford model included in the mathematics book for the sixth grade of primary school (Journal of the College of Basic Education, 2024)
The aim of the current research is: to determine the ratios of the mental abilities of the Guilford model in the content of the mathematics book for the sixth grade of primary school. The descriptive research method was adopted by the method of content analysis, and the research community consisted of a mathematics book for the sixth grade of primary school to be studied by the Iraqi Ministry of Education in the academic year (2021-2022). A list of the mental abilities of the Guilford model was prepared to analyze the content of the mathematics book for the sixth grade of primary school and to determine its warning in the book and its validity, validity and stability of the analysis were verified. After completing the analysis of the book's content, the following was found: The ratios of mental abilities of the Guilford model in the content of the mathematics book for the sixth grade of primary school varied, and not all of them were available at the level of the book as a whole, as the percentages and frequencies of some mental abilities were zero. The two researchers recommended including the content of the mathematics book for the sixth grade of primary school and enriching it with attitudes related to the mental abilities of the Guilford model, especially those that appeared at a weak rate. or zero, and benefit from the content analysis card prepared in this research when making any modification, change or development in the content of the book. To complement the research, they suggested conducting a similar study to identify the percentages of mental abilities of the Guilford model in mathematics books for other primary grades. And evaluating the mathematics book for the sixth grade of primary school according to the Guilford Model of Mental Abilities.